Predicting consistent foraging ecologies of migrating waterbirds: Using stable isotope and parasite measurements as indicators of landscape use. (July 2022) - Sheehan, Kate L.; Dorr, Brian S.; Clements, Stephen A.; Christie, Terrel W.; Hanson-Dorr, Katie C.; Rush, Scott A.; Brian Davis, J.
Highlights: Wildlife disease surveillance programs require large sample sizes that can be supplemented with hunter-caught specimens. Aquaculture facilities provide unique and consistent habitat where hunters can take waterfowl. Reducing waterfowl numbers on fish ponds can reduce economic loss and disease/parasite transmission. Assessments of waterbirds collected near aquaculture for landscape use based on their feeding ecology. Parasites and stable isotopes can be used to differentiate among waterbirds with different feeding strategies when they exist. Abstract: The emergence of novel human pathogens is frequently linked with zoonotic events and human-wildlife interactions that promote disease transmission. Consequently, surveillance of wildlife populations for candidate diseases that could spread to humans is beneficial, but requires widespread collections of numerous samples. A legitimate means to acquire large sample sizes of waterfowl is through cooperation between researchers and hunters, who also work in concert with natural resource managers, landowners, and agricultural entities -e.g., aquaculture facilities. In addition to understanding the occurrence and spread of parasites and pathogens by birds, these samples can be used to answer questions about the ecology of various waterbird species. Body mass and morphometric data on hunter-donated specimen are useful for understanding bird condition and other dynamics of birds; however, when breast meat is removed prior to the acquisition of specimen weight, samples might not be as desirable. Here, we evaluate the utility of data obtained from a bird species that might be targeted by hunters and subsequently used to learn about their disease dynamics. Lesser Scaup ( Aythya affinis ) collected at aquaculture facilities were assessed for their stable isotope concentrations and parasites communities to learn about the birds' foraging ecology. Discriminant analyses designed to classify birds by the aquaculture pond type from which they were collected included isotope data, Principal Components derived from parasite community data of 7 types, and birds' body mass. We compared these to Double-crested Cormorants ( Nannopterum auritum ) feeding on catfish and found the two waterbird species exhibited different infracommunities of parasites Furthermore, some scaup demonstrated fish aquaculture pond type fidelity. Bird body mass was an important metric to include in analytical models when all parasite datatypes were not available. However, the combination of stable isotope concentrations and parasite infracommunity data (that includes prevalence, abundance, volume, and energy use) in models resulted in host ecology differentiation equal or better than models where bird body mass was included. Hunter-derived samples should be encouraged as a means for sample acquisition and be considered as an approach for aquaculture-wildlife conflict management as the information that can be obtained through these samples is multifaceted.